Nitrogen Fertilization Guidelines for Bare-Ground and Plastic Mulch Cabbage Production in Florida: HS1428, 12/2021 - Zotarelli, Lincoln; Barrett, Charles; da Silva, Andre Luiz B. R.; Christensen, Christian; England, Gary (EDIS, 2021)
This new 9-page publication of the UF/IFAS Horticultural Sciences Department focuses on the nitrogen fertilizer best management practices (BMP) for green fresh-market and processing cabbage head production in Florida. This publication aims to provide management strategies that comply with statewide BMP guidelines to optimize economic yield while minimizing nitrogen losses to the environment. Written by L. Zotarelli, C. E. Barrett, A. L. B. R. da Silva, C. T. Christensen, and G. K. England. https://edis.ifas.ufl.edu/hs1428